Profesoras universitarias y cargos de gestión - Marina Tomás i Folch; María del Mar Duran Bellonch; Cristina Guillamón Ramos; José Manuel Lavié Martínez (Universidad de La Rioja, 2013)
In this article we summarize the most relevant findings from a research that purports to incorporate a gender perspective to the study of university management. The study analyzes the role of women in both horizontal and vertical management structures in four Catalan universities, paying attention to their expectations and perceptions. Overall, the results point to the existence of both external and internal barriers that probably explain the lack of women in university management. Among these barriers, organizational culture appears as a change-resist-ant element that promotes an environment dominated by male values and could justify most women's self-exclusion from university management. The study also identifies the main features whereby these women depict their experience in management and attempt to articulate an alternative discourse for leadership in university.